"One stone, two birds": engineering 2-D ultrathin heterostructure nanosheet BiNS@NaLnF4 for dual-modal computed tomography/magnetic resonance imaging guided, photonic synergetic theranostics. Issue 1 (16th December 2020) - Ma, Sihan; Wang, Lin; Liu, Zongjunlin; Luo, Xian; Zhou, Zonglang; Xie, Jun; Li, Yipeng; Cong, Shuo; Zhou, Min; Xu, Yang; Ran, Guang
Abstract : It is interesting yet challenging to design theranostic nanoplatforms for the accurate diagnosis and therapeutics; these single imaging or therapeutic nanoplatforms with own unique shortcomings that limit their widespread bio-medical applications. Abstract : It is interesting yet challenging to design theranostic nanoplatforms for the accurate diagnosis and therapy of diseases; these nanoplatforms consist of single contrast-enhanced imaging or therapeutic agents, and they possess their own unique shortcomings that limit their widespread bio-medical applications. Therefore, designing a potential theranostic agent is an emerging approach for the synergistic diagnosis and therapeutics in bio-medical applications. Herein, a lanthanide-loaded (NaLnF4 ) heterostructure BiOCl ultrathin nanosheet (BiNS@NaLnF4 ) as a theranostic agent was synthesized facilely by a solvothermal protocol. BiNS@NaLnF4 was employed as a multi-modal contrast agent for computed tomography (CT) and magnetic resonance imaging (MRI), showing a high-performance X-ray absorption contrast effect, an outstanding T 1 -weighted imaging function result, good cytocompatibility and favorable in vivo effective imaging for CT. Notably, BiNS@NaLnF4 was applied to achieve a satisfactory photon-thermal conversion efficiency (35.3%). Moreover, the special heterostructure barrier achieved increased utilization of electrons/holes, enhancing the generation of reactive oxygen species (ROS) under visible-light irradiation to further expand the therapeutic effect. Dramatically, visible light emission with the up-conversion law was employed to stimulate ROS after irradiation with a 980 nm laser. Simultaneously, the as-prepared BiNS@NaLnF4 can be applied in photothermal/photodynamic therapy (PTT/PDT) investigation for tumor ablation. In summary, the results reveal that BiNS@NaLnF4 is a potential multi-modal theranostic candidate, providing new insights for synergistic theranostics of tumors.